Investigation of Complex Characteristics of Waterjet Propulsion Device with Intake Grid - Can Luo; Shuaihao Lei; Chuan Wang; Li Cheng; Chenzhi Xia; Di Zhang; Qiang Guo (Shock and Vibration)
The intake grid is always installed technically to protect the impeller at the entrance of the waterjet propulsion device’s inlet duct affecting its performance. Therefore, this study discussed the complex features of the circular, rectangular, and streamlined intake grid. Consistent geometry size of the intake grid mentioned above is to be maintained to guarantee the identical flow capacity at the entrance of inlet duct. Using experimental and simulated method, the outcomes are drawn as below. Rather than the circular and rectangular intake grid, the streamlined intake grid can improve the hydraulic performance of the waterjet propulsion device. The numerical method is proved to be correct as the consistence of the hydraulic characteristic between the test and simulated results. The causes of hydraulic loss in the contraction segment and straight pipe segment are the intake grid and the inflow velocity, respectively; meanwhile, the loss in the belt pipe segment owes to the vortex, flow separation, and impact on the back. The intake grid has a positive effect on the depth of the inlet velocity profile, but a negative effect on the width of it. The intake grid installation results in thrust reduction, the progress of velocity-weighted average angle, and the regress of axial velocity uniformity. The performance of waterjet propulsion device is complex and evaluated by the hydraulic performance index (HPI), thrust performance index (TPI), and characteristic of flow pattern index (CFPI). Based on the three evaluation indexes, the streamlined scheme is raised to be the recommended scheme.